1993
DOI: 10.1080/00288233.1993.10417741
|View full text |Cite
|
Sign up to set email alerts
|

Post-harvest and autumn management of tall fescue seed fields

Abstract: Three post-harvest management systems, burning, grazing, and straw removal, imposed on the stubble of tall fescue (Festuca arundinacea Schreb.) immediately following seed harvest produced similar seed yields in the following season. Autumn defoliation by grazing or cutting produced similar tall fescue seed yields compared to tall fescue plants which were undefoliated from the previous harvest. Applying atrazine (3 kg a.i./ha) initially reduced vegetative tiller numbers but seed yields were not affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 10 publications
(23 reference statements)
3
7
0
Order By: Relevance
“…These factors have a particularly dominant influence on seed yield in the first production year and the effects persist for several successive seed crops. The results confirm the importance of an adequate density of tillers prior to winter for seed yield of tall fescue (Robson 1968;Hare 1992Hare , 1993Hare , 1994. The pattern of response of seed yield to plant density was similar for each of the three row spacings in this study.…”
Section: Discussionsupporting
confidence: 74%
“…These factors have a particularly dominant influence on seed yield in the first production year and the effects persist for several successive seed crops. The results confirm the importance of an adequate density of tillers prior to winter for seed yield of tall fescue (Robson 1968;Hare 1992Hare , 1993Hare , 1994. The pattern of response of seed yield to plant density was similar for each of the three row spacings in this study.…”
Section: Discussionsupporting
confidence: 74%
“…Based on these studies, and on others from the USA (Watson and Watson 1982;Albeke et al 1983;Chastain and Grabe 1989) and Japan (Suzuki 1989), which each reported a maximum density of reproductive tillers of 400 to 600 m -2 , Hare (1993) agreed with the earlier interpretation of Robson (1968) that the density of reproductive tillers in tall fescue may be limited genetically, and that insufficient nutrient resources may preclude the attainment of reproductive tiller densities as high as 1000 to 2000 m -2 . The present results do not support the existence of such a limitation.…”
Section: Discussionsupporting
confidence: 72%
“…The dependence of tall fescue seed yield on the number of panicles m -2 has been well documented in New Zealand by Hare (1992Hare ( , 1993Hare ( , 1994 who also found that fertile tiller density was particularly important for the first seed crop (Hare 1994). Based on these studies, and on others from the USA (Watson and Watson 1982;Albeke et al 1983;Chastain and Grabe 1989) and Japan (Suzuki 1989), which each reported a maximum density of reproductive tillers of 400 to 600 m -2 , Hare (1993) agreed with the earlier interpretation of Robson (1968) that the density of reproductive tillers in tall fescue may be limited genetically, and that insufficient nutrient resources may preclude the attainment of reproductive tiller densities as high as 1000 to 2000 m -2 .…”
Section: Discussionmentioning
confidence: 99%
“…Research on perennial forage, turf, and native grasses indicates that both defoliation and increasing row spacing influence grain yield by modifying tiller density. Increasing the number of fertile tillers per unit area can improve perennial grass seed yield (Deleuran, Gislum, & Boelt, 2009 and 2010; Han et al., 2013), but at a certain tiller density this relationship saturates (Aamlid, Heide, Christie, & McGraw, 1997; Hampton & Fairey, 1997; Hare, 1993). Competition among tillers results in a cascade of compensatory responses among yield components (YCs), affecting first tiller fertility, then spikelets per fertile tiller, florets per spikelet, seeds per floret, and seed size (Hampton & Fairey, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Due to these compensatory responses, in many cases management interventions that strongly influence one yield component do not affect seed yield (Deleuran et al., 2009 and 2010; Hampton & Fairey, 1997; Han et al., 2013; Hare, 1993; Koeritz, Watkins, & Ehlke, 2015; Young, Youngberg, & Chilcote, 1996). Seed number per fertile tiller is typically the YC with the strongest effect on total yield (Hampton & Fairey, 1997; Hebblethwaite & Clemence, 1981; Hebblethwaite & Ivins, 1977).…”
Section: Introductionmentioning
confidence: 99%